ENHANCING STUDENT COMPETENCIES IN OPERATIONAL MANAGEMENT AND HUMAN RESOURCE PRACTICES THROUGH INDUSTRIAL VISIT AT JOHOR CERAMICS FACTORY - Jefri Damuri Hutauruk; Sulaiman Sulaiman; Vita Setiati; Debi Marianti; Rita Indriani; Andika Pratama; Mia Wulandari; Tri Utama; Hanafi Siregar; Habibuddin Nasution; Umi Kartini Binti Rashid; Mohd Asmadi Bin Mohd Angsor; Nur Aina Binti Azizan; Nur Athirah Binti Mohd Borkhan; Mohd Khairul Naser Bin Ibrahim (RADJA PUBLIKA, 2026)
This study aims to enhance student competencies in operational management and human resource (HR) practices through an industrial visit to Johor Ceramics Factory, Malaysia. The activity employs an experiential learning approach that integrates field observation, semi-structured interviews with managers and HR supervisors, and student reflective discussions. This method provides practical understanding of production flow, quality control, shift management, employee training, and motivation and incentive systems. Data were collected through participatory observation, interviews, documentation, and focus group discussions, then analyzed using qualitative descriptive analysis with thematic coding and theory-practice comparison. The results show that students were able to integrate management theory with actual factory practices, enhancing operational understanding, analytical skills, critical thinking, collaboration, and reflection. Additionally, the activity benefits industry partners through recommendations for improving efficiency and HR management. Academic implications indicate that industrial visits support curriculum development based on experiential learning and service-learning, ensuring student competencies develop holistically and practically. This model can serve as an effective integrative learning strategy in higher education while providing tangible contributions to industry and student professional learning.